Sikap Ibu Rumah Tangga Terhadap Tes HIV/AIDS di Sleman Yogyakarta - Nanik Setiyawati; Zahroh Shaluhiyah; Kusyogo Cahyo (Jurnal Promosi Kesehatan Indonesia, 2014)
ABSTRAKKasus HIV/AIDS pada ibu rumah tangga semakin meningkat dan di Kecamatan Sleman telah terdapat kasus kematian ibu rumah tangga. Tes HIV/AIDS menjadi pintu gerbang program penanganan dan pencegahan HIV/AIDS, namun belum ada kunjungan masyarakat untuk VCT di Puskesmas Sleman. Penelitian ini untuk mengetahui sikap ibu rumah tangga terhadap tes HIV/AIDS di Sleman. Jenis penelitian ini adalah penelitian kualitatif dengan Focus Group Discussion (FGD) dan triangulasi dengan indepth interview. Informan berjumlah 48 orang yang terbagi dalam 8 kelompok FGD dan informan sekunder 2 orang untuk triangulasi. Analisis data dengan content analysis. Hasil penelitian ini menggambarkan bahwa seluruh kelompok ibu rumah tangga mendukung tes HIV/AIDS. Kelompok ibu rumah tangga dengan suami bukan kelompok rentan tertular HIV menganggap ibu rumah tangga tidak mungkin tertular HIV dan laki-lakilah yang harus tes HIV. Hanya kelompok ibu rumah tangga yang berdomisili di desa peduli HIV/AIDS yang tahu tentang definisi, penyebab, penularan, pengobatan, perawatan HIV/AIDS dan tes HIV/AIDS. Sikap seluruh kelompok ibu rumah tangga terhadap tes HIV/AIDS dipengaruhi oleh sikap suami terhadap tes HIV/AIDS.Kata kunci : sikap, ibu rumah tangga, tes HIV/AIDSABSTRACTAttitudes Towards Testing For HIV/AIDS Among Housewife In Sleman Yogyakarta; Cases of HIV/AIDS on housewives is increasing and in Sleman district there have been cases of death of a housewife. HIV/AIDS testing is the gateway program management and prevention of HIV/AIDS, but no visits to the health center VCT in Sleman. Study was to determine the attitude of the housewife to test HIV/AIDS in Sleman. This research is a qualitative research Focus Group Discussion (FGD) and triangulation with indepth interview. Informants totaling 48 people, divided into 8 groups of FGD and 2 people for triangulation. Data analysis with content analysis. The results of this study illustrate that the entire group of housewives support HIV/AIDS test. The group housewife with a husband instead of contracting HIV vulnerable groups considered unlikely housewives infected with HIV and men who have an HIV test. Only the group of housewives who live in the village of care HIV/AIDS who knows about the definition, causes, transmission, treatment HIV/AIDS and HIV/AIDS testing. The attitude of the whole group of housewives to test for HIV/AIDS affected by the husband’s attitude towards HIV/AIDS test.Keywords: Attitudes, housewife, testing for HIV / AIDS